Covid-19 infection in patients with autoimmune rheumatic diseases: Patient’s perspective and descriptive analysis from a lower-middle-income country - Riaz, Mehmood; Ishaq, Saliha; Zaibunnisa; Jibril, Huzefa; Mahmood, Saad Bin Zafar (Journal of the Pakistan Medical Association, 2023)
The study was conducted to determine the severity of Covid-19 in autoimmune inflammatory rheumatic disease (AIRDs) patients and knowing their perceptions. All AIRDs cases with Covid-19 infection between December 2020 and February 2021 were included. A cross-sectional phone survey was conducted for perceptions. Twenty-one patients were analysed for severity of illness and 16 (76.2%) for perceptions. Mean age was 44.8 ±14.8 years, with 11 (52.4%) females. Two (9.5%) patients had severe disease, six (28.6%) required hospitalisation, and none expired. Hypertension 7 (33.3%) was the commonest comorbidity. Low dose steroids were the most used drug 9 (42.9%). Regarding perceptions, 10 out of 16 (62.5%) felt that AIRD made them vulnerable to Covid-19 infection. The most common reason of delay in seeking medical advice from the rheumatologist was closure of services for chronic diseases during the pandemic. ---Continue